Pengaruh Ukuran Perusahaan, Solvabilitas, dan Profitabilitas terhadap Audit Delay (Study empiris pada perusahaan perbankan yang terdaftar di Bursa Efek Indonesia) - Alawiah, Magfira; Hasibuan, David HM (Institut Bisnis dan Informatika Kesatuan, 2019)
Timeliness in financial reporting is an obligation for companies listed on the Indonesia Stock Exchange to submit periodic financial report. Delay in financial reporting will have a negative effect on a company, because it may indicate the existence of financial problem within the company. The length of time of an audit conducted by an auditor can be seen from the time different between the financial statment date and the date the auditor’s report was signed in the financial statement. The time different is often called an audit delay. The longer the auditor completes the audit, the longer the audit delay is. If the audit delay is long, the delay in submitting financial statment to stakeholders will be longer. Prompt financial reporting is essential to maintain the accuracy of information presented in the financial statement. The purpose of this study is to identify and explain the influence of Firm Size, Solvability, and Profitability to Audit Delay. The population used is Banking Company listed on Indonesia stock Exchange during the period 2015-1017. The variables used in this research are Firm Size, Solvability, and Profitability. The data used is the company’s financial statements are published through the website www.idx.co.id. Data colletion method used is purposive sampling method. Analysis of the data in this study using classic assumption test, multiple linear regressioin analysis and hypothesis testing. Based on the research that has been done can be the concluded that the partial factor Firm Size significant effect on Audit Delay while the Solvability and Profitability has no significant effect on Audit Delay. Simultaneously factor Firm Size, Solvability and Profitability effect on audit Delay the R Square value is 0.242 indicates that 24,2% of Audit Delay cab be explained by the independent variables used in the study, while the remaining 75,8% is explained by other variables.